SOME FACTORS INFLUENCING IN STUDENT ACHIEVEMENT - Tai Sarula (International Journal of Innovative Technologies in Social Science, 2025)
The economic situation, study and homework habits, time management, health status, and family relationships all impact the academic success of students. This study aims to identify the factors that have the most impact on student academic achievement. The factors that impact students' academic success are classified into four groups according to their perception: the teacher's role, school culture, learning environment, and parental involvement. The goal of the research is to present the outcomes by utilizing the research that reveals each specific indicator from the students. The academic success of students can be affected by many factors, but those linked to the student's personality are the most important. The achievement of students is regarded as a crucial indicator of excellent academic performance. This study mainly focuses on investigating the influences of teacher, student, school, and family factors on students’ achievement. Few study reviews were made on the absolute factors which influence their achievement.